Field-emitter cathode for acceleration sensors - Hariz, A.; Kim, H.G.; Haskard, M.R.; Chung, I.J. (1995)
Vacuum microelectronics is an emerging and rapidly evolving technology. Characterized by field emission in vacuum microchambers, it has found applications in the display field, and more recently in sensor technology. In this paper we seek to report on a novel multidimensional method of utilizing field emission in acceleration sensors. Emission currents are directly related to, among other parameters, the distance separating the emission cathode and anode. When either or both electrodes are micromachined in a cantilever beam capable of deflection under the influence of an external force, the emission current detected will be a direct measure of force magnitude. Furthermore, we propose a design that will allow measurements of force components in three-dimensions. We present details of fabrication methods and theoretical concepts describing the mechanism proposed. ？ 1995 IOP Publishing Ltd.
Keywords: Acceleration sensors; Field emitter cathode; Fowler-Nordheim tunnelling equation; Vacuum microchambers; Vacuum microelectronics; Acceleration; Electric breakdown; Electric currents; Electric fields; Electron tunneling; Fabrication; Microelectronics; Sensors; Three dimensional; Vacuum; Cathodes